Conteúdos de interpretar: a leitura como passaporte para a interação com o mundo - Viegas, Ilana da Silva Rebello (2009)
This study is based on a series of activities of comprehension and interpretation of texts, performed by public school students, from different grade levels, as well as by teachers who are responsible for teaching suc h contents. Such analysis showed that, in general, students have difficulties to understand and interpret what they read, independently of their grade level, and also that there are interpretation contents that are not dealt with in a systematic way in schools. Thus, having as a scope the Semiolinguistic Theory of Discourse Analysis, the presuppositions of Text Linguistics, focusing particularly on the text, production of meanings, and the didactic sequences approach (Dolz & Schneuwly: 2004), we propose interpretation contents and present suggestions of activities in didactic sequences, involving content related to interpretation, departing from organizational modes of discourse, configured in different genres. More than a didactic proposal, it is an attempt to improve the teaching so impoverished in school of reading of different texts.